Compressive buckling performance of multilayer laminated glass columns with different interlayers. (15th April 2023) - Lu, Yujia; Zhao, Suinan; Chen, Suwen
Highlights: 30 PVB/SG laminated glass columns were compressively tested. Failure is caused by flexural buckle. A tensile-stress-controlled design buckling curve was proposed and validated. Quasi-elastic method can be used with viscoelastic interaction considered. Rubbery limit applies for PVB columns but is conservative for SG ones. Abstract: Multilayer laminated glass columns have been widely used instead of monolithic ones. The lack of test data of columns with ionomer interlayers, a general and unified formula for determining the buckling resistance, and a well-proven design method limits the application of laminated glass columns. To this end, compressive tests were conducted on multilayer laminated glass columns, taking the height and sectional configuration (thickness, glass layers and interlayer types) as variables. The comparison between test, numerical and analytical results emphasizes the applicability of the existing formulae in determining buckling resistance and the attention to the viscoelastic interaction. Then, a tensile-stress-controlled buckling curve was proposed and validated based on the present and published data. Finally, a comparative study based on the full viscoelastic methods implies that the quasi-elastic approximation can be adopted when the interlayers' viscoelasticity is considered. The rubbery limit can be used as the designed buckling resistance for columns with polyvinyl butyral (PVB) but is conservative for those with an ionomer interlayer.